2011
DOI: 10.1128/jvi.05562-11
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus RNA-Dependent RNA Polymerase Is Phosphorylated by an Important Survival Kinase, Akt

Abstract: Viruses commonly use host cell survival mechanisms to their own advantage. We show that Akt, an important signaling kinase involved in cell survival, phosphorylates the RNA-dependent RNA polymerase (RdRp) from norovirus, the major cause of gastroenteritis outbreaks worldwide. The Akt phosphorylation of RdRp appears to be a feature unique to the more prevalent norovirus genotypes such as GII.4 and GII.b. This phosphorylation event occurs at a residue (Thr33) located at the interface where the RdRp finger and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Indeed, growing numbers of virus-encoded phosphoproteins implicated in viral pathogenesis, virion assembly, and genome replication have been identified recently (2)(3)(4)(5)(6)(7). In plus-strand RNA viruses, including hepatitis C virus (HCV), the viral RNA genome is replicated by virus-encoded RNA-dependent RNA polymerases (RdRps) (7), and their phosphorylation has been suggested to be functionally linked to viral genome replication (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Indeed, growing numbers of virus-encoded phosphoproteins implicated in viral pathogenesis, virion assembly, and genome replication have been identified recently (2)(3)(4)(5)(6)(7). In plus-strand RNA viruses, including hepatitis C virus (HCV), the viral RNA genome is replicated by virus-encoded RNA-dependent RNA polymerases (RdRps) (7), and their phosphorylation has been suggested to be functionally linked to viral genome replication (6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…These multiple effects of Akt/PKB can modulate cap-versus internal ribosome entry site (IRES)-dependent translation as well as infected-cell survival, which may facilitate virus persistence. Thus, not surprisingly, several viral proteins can modulate PI3K/Akt-dependent signaling pathways (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Recent work has suggested that Akt may phosphorylate the phosphoprotein of several negative-stranded RNA viruses 60 and that it may also control calicivirus polymerase function. 133 Future discoveries will likely greatly expand the number of viral substrates and more clearly point out the viral dependencies on this signaling axis.…”
Section: Discussionmentioning
confidence: 99%